POLICY ACTORS AND POLICY ISSUES FOR RELIGION IN PUBLIC DIALOGUE AND PEACEMAKING (Annual of the Faculty of Philosophy in Skopje, 2024)
The purpose of this article is to establish a connection between key policy actorsand significant policy issues regarding religion in public discourse and peacebuildingwithin a broader context. The challenge lies in addressing the dilemmas surroundingwhether discussions about religion, its impact on younger generations, and its role inpeacemaking are solely influenced by religious factors, or if other social and political actorsplay a role as well. Through our research, we have identified ongoing political processesthat have the potential to enhance religious dialogue and peacemaking on variouslevels. This mapping of actors and processes has been informed by literature, establishedacademic and social networks like Culturelink (a Network of Networks for Researchand Cooperation in Cultural Development, established by UNESCO and the Councilof Europe), web searches, and interviews with stakeholders. The result of this analysisis a comprehensive list of over 300 actors documented in the RETOPEA Horizon 2020project. We contend that current political processes offer opportunities to strengthendialogue, which is more robust in some European countries but lacking in others when itcomes to addressing issues related to the resurgence of religion in international politicsand peacebuilding efforts.
Keywords: religion; dialogue; policy actors and processes; peacebuilding